2020
DOI: 10.3390/nu12020505
|View full text |Cite
|
Sign up to set email alerts
|

A Delayed Morning and Earlier Evening Time-Restricted Feeding Protocol for Improving Glycemic Control and Dietary Adherence in Men with Overweight/Obesity: A Randomized Controlled Trial

Abstract: We determined the effects of time-restricted feeding (TRF; 8 h/d) versus extended feeding (EXF; 15 h/d) on 24-h and postprandial metabolism and subjective opinions of TRF in men with overweight/obesity. In a randomized crossover design, 11 sedentary males (age 38 ± 5 y; BMI: 32.2 ± 2.0 kg/m2) completed two isoenergetic diet protocols for 5 days, consuming meals at 1000, 1300 and 1700 h (TRF) or 0700, 1400 and 2100 h (EXF). On Day 5, participants remained in the laboratory for 24 h, and blood samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 118 publications
(180 citation statements)
references
References 36 publications
4
146
0
4
Order By: Relevance
“…Here, we interrogated the skeletal muscle transcriptome, and serum and skeletal muscle metabolome of men with overweight/obesity, to determine how restricting the window of food intake (from 15 to 8 h day −1 ) confers some of the metabolic health benefits that have been reported after TRF 8,12 . In this cohort, short-term TRF reduced nocturnal glucose levels and improved insulin profiles throughout the day 15 . Serial sampling of serum and skeletal muscle over a 24-h period provides a comparative analysis of the diurnal metabolome in serum versus skeletal muscle in humans and is critical to decipher those circulating metabolites that constitute specific metabolic signatures of differential nutritional challenges.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Here, we interrogated the skeletal muscle transcriptome, and serum and skeletal muscle metabolome of men with overweight/obesity, to determine how restricting the window of food intake (from 15 to 8 h day −1 ) confers some of the metabolic health benefits that have been reported after TRF 8,12 . In this cohort, short-term TRF reduced nocturnal glucose levels and improved insulin profiles throughout the day 15 . Serial sampling of serum and skeletal muscle over a 24-h period provides a comparative analysis of the diurnal metabolome in serum versus skeletal muscle in humans and is critical to decipher those circulating metabolites that constitute specific metabolic signatures of differential nutritional challenges.…”
Section: Discussionmentioning
confidence: 67%
“…Sample size was choosen based on previous published research 14,31 . Clinical characteristics of the study participants have been previously reported 15 . First enrollment of participants was on 30/01/2017, and trial was completed by 22/06/2017.…”
Section: Methodsmentioning
confidence: 99%
“…Energy consumption after 19:00 h contributed to the majority of the non-adherent occasions (63%), corresponding to the largest energy intake period over a day [3,33]. In men with overweight/obesity, consuming an earlier dinner (17:00 vs. 21:00 h) induced greater peak insulin concentration and a trend for lower glucose incremental area under the curve in previous research [44]. As there is evidence that eating even earlier (by 15:00 h) can improve ß-cell function and 24-h glucose concentrations [7,8], TRE may be a useful strategy to limit end of day eating and post-dinner snacking of discretionary foods (e.g., ice cream and chocolate) and alcohol.…”
Section: Discussionmentioning
confidence: 70%
“…While various measures of glycaemic control have been improved in previous ad libitum and energy-matched TRE interventions of varying durations (4 days to 12 weeks), all previous investigations have been in those with normal or impaired glucose tolerance [4,5,[7][8][9]27,44,48]. Individuals with T2D have altered circadian patterns of glucose regulation [17,49], with greatest impairments to glucose tolerance in the morning compared to the evening in those with normal or impaired glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation